2016
DOI: 10.1002/ese3.123
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/TiO2 double layer anti‐reflection coating film for crystalline silicon solar cells formed by spray pyrolysis

Abstract: An Al 2 O 3 /TiO 2 double layer anti-reflection coating (ARC) film formed by spray pyrolysis was introduced for monocrystalline silicon solar cells as the nonvacuum processing method. The thickness of the Al 2 O 3 layer and TiO 2 compact layer was controlled by the volume of deposited precursor solution and confirmed by ellipsometry and scanning electron microscopy. The average photovoltaic properties of photocurrent density (J sc ), open-circuit photovoltage (V oc ), fill factor (FF), and photo energy convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Although it was shown that the vacuum-less processed TiO 2 , Al 2 O 3 , and ZrO 2 based ARC layers were promising, the power conversion efficiencies were limited to around 16%. The main drawback of those vacuum-less processed solar cells was the insufficient front surface passivation, even though the average reflectance (300-1100 nm) of the textured silicon surface with ARC could be reduced significantly down to below 7% [16][17][18]. In this study, SiO 2 layer formation upon thermal oxidation was performed by O 2 /H 2 O bubbling and a SiO 2 /TiO 2 stack layer was formed with spray deposited TiO 2 film for further improvements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it was shown that the vacuum-less processed TiO 2 , Al 2 O 3 , and ZrO 2 based ARC layers were promising, the power conversion efficiencies were limited to around 16%. The main drawback of those vacuum-less processed solar cells was the insufficient front surface passivation, even though the average reflectance (300-1100 nm) of the textured silicon surface with ARC could be reduced significantly down to below 7% [16][17][18]. In this study, SiO 2 layer formation upon thermal oxidation was performed by O 2 /H 2 O bubbling and a SiO 2 /TiO 2 stack layer was formed with spray deposited TiO 2 film for further improvements.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent studies, we have been introduced TiO2, Al2O3, and ZrO2 single or double layers based on spin coating or spray pyrolysis methods [16][17][18]. Those results were remarkable to suggest low temperature and non-vacuum processed ARC film as an alternative to mainstream silicon nitrate based films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In depth analysis was carried out with fitting models of "flat layer" as the main body of the coated layer and "rough layer" as the surface residue when depositing a spraydeposited TiO 2 and Al 2 O 3 films [21] and fitted according to the real SEM images. As an optimum value of 60 mL TiO 2 and 100 mL Al 2 O 3 precursor solutions were considered.…”
Section: Characterization Of the Filmsmentioning
confidence: 99%